2009
DOI: 10.1128/mcb.01856-08
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisome Proliferator-Activated Receptor γ/Retinoid X Receptor α Heterodimer Targets the Histone Modification Enzyme PR-Set7/Setd8 Gene and Regulates Adipogenesis through a Positive Feedback Loop

Abstract: Control of cell differentiation occurs through transcriptional mechanisms and through epigenetic modification. Using a chromatin immunoprecipitation-on-chip approach, we performed a genome-wide search for target genes of peroxisome proliferator-activated receptor ␥ (PPAR␥) and its partner protein retinoid X receptor ␣ during adipogenesis. We show that these two receptors target several genes that encode histone lysine methyltransferase SET domain proteins. The histone H4 Lys 20 (H4K20) monomethyltransferase PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(233 citation statements)
references
References 34 publications
(36 reference statements)
5
221
0
Order By: Relevance
“…ChIP was performed as described previously (Kaneshiro et al, 2007;Wakabayashi et al, 2009) with some modifications. Briefly, for ChIP-quantitative PCR (qPCR), AHP cells were harvested, and genomic DNA was cross-linked using 1% formaldehyde overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP was performed as described previously (Kaneshiro et al, 2007;Wakabayashi et al, 2009) with some modifications. Briefly, for ChIP-quantitative PCR (qPCR), AHP cells were harvested, and genomic DNA was cross-linked using 1% formaldehyde overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…108 In a feedback loop, the H4K20 HMT Set7/Setd8 is upregulated by PPARg during adipogenesis, at the time that this enzyme positively regulates the expression of PPARg and its target genes trough H4K20 monomethylation.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Decrease of H3K27/H3K9 methylation is observed in adipogenic promoters, accompanied by increased histone acetylation and H3K4/ H3K20 methylation. 38,50,108 Another characteristic feature during terminal differentiation of adipocytes is the spread of di and tri-methylation of H3K4, acetylation of H3 and the Pol II to the coding region of the adipogenic genes, coinciding with high levels of transcription of those genes. 38,50 in cell differentiation, including adipogenesis.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
“…A genomic screen found that H4K20me-1 was enriched in the coding regions of active genes, hinting at a positive role of H4K20me-1 in gene transcription (12). More recent evidence has shown that SET8 and H4K20me-1 play a positive role in peroxisome proliferator-activated receptor (PPAR)γ expression and adipogenesis (13).…”
mentioning
confidence: 99%